Acerola (Malpighia emarginata DC.) juice intake protects against alterations to proteins involved in inflammatory and lipolysis pathways in the adipose tissue of obese mice fed a cafeteria diet - Dias, Fernando Milanez; Leffa, Daniela Dimer; Daumann, Francine; Marques, Scherolin de Oliveira; Luciano, Thais F.; Possato, Jonathan Correa; Santana, Aline Alves de; Neves, Rodrigo Xavier; Rosa, Jose Cesar; Oyama, Lila Missae; Rodrigues, Bruno; Andrade, Vanessa Moraes de; et al. (Biomed Central Ltd., 2014)
Background: Obesity has been studied as a metabolic and an inflammatory disease and is characterized by increases in the production of pro-inflammatory adipokines in the adipose tissue. To elucidate the effects of natural dietary components on the inflammatory and metabolic consequences of obesity, we examined the effects of unripe, ripe and industrial acerola juice (Malpighia emarginata DC.) on the relevant inflammatory and lipolysis proteins in the adipose tissue of mice with cafeteria diet-induced obesity.Materials/methods: Two groups of male Swiss mice were fed on a standard diet (STA) or a cafeteria diet (CAF) for 13 weeks. Afterwards, the CAF-fed animals were divided into five subgroups, each of which received a different supplement for one further month (water, unripe acerola juice, ripe acerola juice, industrial acerola juice, or vitamin C) by gavage. Enzyme-linked immunosorbent assays, Western blotting, a colorimetric method and histology were utilized to assess the observed data.Results: The CAF water (control obese) group showed a significant increase in their adiposity indices and triacylglycerol levels, in addition to a reduced IL-10/TNF-alpha ratio in the adipose tissue, compared with the control lean group. In contrast, acerola juice and Vitamin C intake ameliorated the weight gain, reducing the TAG levels and increasing the IL-10/TNF-alpha ratio in adipose tissue. In addition, acerola juice intake led to reductions both in the level of phosphorylated JNK and to increases in the phosphorylation of I kappa B alpha and HSLser660 in adipose tissue.Conclusions: Taken together, these results suggest that acerola juice reduces low-grade inflammation and ameliorates obesity-associated defects in the lipolytic processes.
Keywords: Cafeteria diet; Malpighia emarginata DC; Adipose tissue; Inflammation; Lipolysis